2008
DOI: 10.1016/j.ajhg.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Linkage Analysis of a Parkinsonian-Pyramidal Syndrome Pedigree by 500 K SNP Arrays

Abstract: Robust SNP genotyping technologies and data analysis programs have encouraged researchers in recent years to use SNPs for linkage studies. Platforms used to date have been 10 K chip arrays, but the possible value of interrogating SNPs at higher densities has been considered. Here, we present a genome-wide linkage analysis by means of a 500 K SNP platform. The analysis was done on a large pedigree affected with Parkinsonian-pyramidal syndrome (PPS), and the results showed linkage to chromosome 22. Sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
197
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(200 citation statements)
references
References 38 publications
0
197
0
3
Order By: Relevance
“…A homozygous mutation in the FBXO7 gene was identified in an Iranian family with early-onset autosomal recessive parkinsonism and pyramidal tract signs [180]. Another homozygous mutation and a compound heterozygous mutation were found in Italian and Dutch families with similar phenotypes [261].…”
Section: Park15mentioning
confidence: 94%
See 1 more Smart Citation
“…A homozygous mutation in the FBXO7 gene was identified in an Iranian family with early-onset autosomal recessive parkinsonism and pyramidal tract signs [180]. Another homozygous mutation and a compound heterozygous mutation were found in Italian and Dutch families with similar phenotypes [261].…”
Section: Park15mentioning
confidence: 94%
“…To date (2010), 11 genes and an additional 3 genetic loci have been associated with PD [168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184]; two additional loci await to be confirmed [185,186]. The PD genes and loci are described in Table 4.…”
Section: Genes and Loci In Familial Pdmentioning
confidence: 99%
“…Fbxo7 had a nuclear localization in a percentage of biopsies from human colon cancer samples, and yet, interestingly, data presented here indicated a different localization defect in PD. Homozygous inheritance of an R378G allele of Fbxo7 causes an atypical PD (9,11), and finding that this pathogenic point mutation, located outside of the FBD, severely compromised Skp1 binding was surprising. Moreover, in agreement with our model for the role of Skp1 binding in nuclear retention, R378G did not accumulate in the nucleus and was more cytoplasmic than the WT protein.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal recessive mutations in FBXO7 have been identified as causing an early-onset Parkinsonian disease (9,11), and Fbxo7 has also been found to be highly expressed in human malignancies (10). We cloned Fbxo7 in a yeast two hybrid screen for proteins interacting with viral D-type cyclins (10).…”
mentioning
confidence: 99%
“…Additionally, Cytochrome P450 (CYP), and in particular CYP2D6, which has polymorphic expression, and which is expressed in neurons and in the gut has a different expression in PD patients, where it has been found preponderantly as CYP2D6*4 allele [267] CYP2D6 acts as a 25-hydroxylase, which is able to convert vitamin D3 into 25OHD, being the key enzyme to determine a deficiency of vitamin D. In mouse MPTP treated model (inducing PD phenotype), Singh et al [268] reported the strong expression of the animal ortholog of CYP2D6, CYP2D22. Very interestingly, CYP2D loci are located on chromosome 22 where many genes related to PD are segregated [269][270][271]. It seems surprising that deletion of chromosome 22q11 was reported to be associated to PD [271] but also with a reduced serum calcium and a reduced level of vitamin D [272].…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 99%